232 Patient Perception of Penile Size and Device after Penile Implant Revision for Mechanical Failure. Issue 1 (1st April 2022) - Habashy, E; Ziegelmann, M; Helo, S; Trost, L; Kohler, T
ABSTRACT: Introduction: IPP revision after implant malfunction yields rare insight into patient preference and perception of penile implant variations in brand and size. Objective: To assess patients' perception of their penile implant after IPP revision. Methods: Retrospective review of all patients undergoing revision surgery for purely mechanical malfunction (fluid leak) at our institution since 2017. Patients with greater than 6 months follow-up after revision were contacted to comment on changes in penile size and device preference. Patients were asked 1. "Did you notice any change in penile length or girth after your last surgery, explain, and 2. "Please describe your preference (if any) of implant and why". We utilize the Coloplast Titan with "classic" (genesis) pump in most cases, with AMS Cx cylinders being used in cases with attenuated corpora (aneurysm). Results: 21 patients were identified that met criteria with an average age of 70. 15/21 were successfully contacted. 9 Coloplast, 2 Mentor, and 12 AMS devices (Cx =7, LGX =4, Ultrex =1) were revised. Device brand used to replace the broken IPP was n= 19 for Coloplast and n=3 for AMS (Cx =2, Lgx =1). Mean and median time to revision was 9 years overall (2-26) and was similar between Coloplast and AMS. Fluid leak location showed no discernable pattern. Total average implant length increased 2.2 cm from 20.6 cm to 22.8 cm. 8/10 patients were reached that had had both AMS and Coloplast devices (all AMS initially). 12 patients stayed within the manufacturer. Despite change in implanted length, most patients did not discern a definitive change in penile length unless cylinders increased by > 3 cm (perhaps reflecting under-sizing of initial implant). All patients correctly described improvement or no change in penile girth when compared to actual cylinder sizes. Patients preferred Coloplast (6 – girth/erection quality/pump), AMS (1 pump/flaccidity) and undecided (1). Several patients felt consistently cycling the device after revision led to relative length improvement and ease of use. Conclusions: Our small cohort of IPP revision patients for mechanical failure reveals that revision often requires longer cylinders but this is often imperceptible to the patient. Increased cylinder girth was a key factor in driving device preference. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Senior author consultant for Coloplast